PENGARUH REGULASI INVESTASI PROVINSI RIAU TERHADAP REALISASI PENANAMAN MODAL ASING (PMA) PROVINSI RIAU (2017-2021) - Alvia, Annisaa; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Since the decentralization or regional autonomy policy in 2001, it has authorized local governments to regulate their government. Regulation of foreign investment and also resulted in a conducive investment climate in the region. Indonesia The issuance of Law Number 25 of 2007 concerning Investment regulates regulations and basic policies in Investment in Indonesia. In addition, the Riau Provincial Government issued Riau Provincial Regulation Number 10 of 2017 concerning the Provision of Incentives and Ease of Investment and Regional Regulation Number 7 of 2018 concerning Investment of Riau Province. This makes the realization of PMA in Riau Province PMA in the second quarter of 2021 reach its peak in 5 business sectors. This qualitative research uses data collection techniques derived from books, journals, scripts, official documents, reports and websites that have relevance to the research. This study also uses the perspective of liberalism with the level of national state analysis, as well as the theory of fiscal decentralization. The results of this study show that since the issuance of the Riau Provincial PMA regulation, namely: 1) Riau Provincial Regulation Number 10 of 2017 on Providing Incentives and Ease of Investment; 2) Riau Provincial Regulation Number 7 of 2018 on Investment) Riau Governor Regulation Number 52 of 2018 on Instructions Implementation of Local Regulation and Regulation Number 10 of 2017 on Incentives for Ease of Investment 4) Riau Governor Regulation Number 6 of 2019 concerning General Plan for Investment of Riau Province in 2019-2025. Since the issuance of the regulation, the number of investment realizations in Riau Province has increased by 1,919,314.70 (Million US), the percentage of Indonesian migrant workers increased by 58.08% and the GDP of Riau Province from IDR 558,492.72 billion before the regulation, to IDR 704,705.03 billion after the regulation. Keywords: Regional Autonomy, Regulation, Foreign Direct Investment, Provincial Regulation